Silver point modified carbon nitride / urea-perylene bisimide heterojunction material as well as preparation method and application thereof

By modifying the carbon nitride/urea-peryleneimide heterojunction material in silver dots, the problems of low photogenerated carrier separation efficiency and weak redox capacity of existing photocatalytic materials during the antibiotic degradation process are solved, and the ability of full-spectrum catalytic mineralized antibiotics is achieved, and the antibiotic degradation efficiency and material stability are improved.

CN119733556APending Publication Date: 2025-04-01YUNCHENG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411941127.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing photocatalytic materials have problems such as low separation efficiency of photogenerated carriers, weak redox capabilities, and inability to effectively utilize near-infrared light during the antibiotic degradation process, which limits their application in the field of wastewater purification.

Method used

Silver dots are used to modify carbon nitride/urea-peryleneimide heterojunction material. This material forms an S-type heterojunction through self-assembly of K gradient doped carbon nitride and urea-peryleneimide. Combined with the resonance effect of Ag quantum dots, the separation efficiency and redox capacity of photogenerated carriers are significantly improved.

Benefits of technology

The full spectrum catalytic mineralized antibiotic capability of the material is significantly improved, the degradation efficiency of the antibiotic is enhanced, and good stability and cycling performance under visible and near-infrared light irradiation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005212594110000011
    Figure HDA0005212594110000011
  • Figure HDA0005212594110000012
    Figure HDA0005212594110000012
  • Figure HDA0005212594110000013
    Figure HDA0005212594110000013
Patent Text Reader

Abstract

The invention provides a silver dot modified carbon nitride / urea-perylene bisimide heterojunction material and a preparation method and application thereof. The heterojunction material is an S-shaped heterojunction formed by Ag quantum dots, carbon nitride and urea-perylene bisimide. Wherein the carbon nitride is K gradient doped carbon nitride. The preparation method comprises the following steps: S1, grinding and mixing graphite-like carbon nitride powder and KCl powder, and calcining, washing, drying and grinding the mixture to obtain carbon nitride powder; s2, dispersing the carbon nitride powder and the urea-perylene bisimide powder into absolute ethyl alcohol, adding AgNO3 powder, and stirring to obtain a reaction precursor solution; and S3, carrying out solvothermal reaction on the reaction precursor solution, and washing and drying a product to obtain the silver point modified carbon nitride / urea-perylene bisimide heterojunction material. The separation efficiency and redox capacity of photon-generated carriers of the material are remarkably improved, and the material shows enhanced capacity of full-spectrum catalytic mineralization of antibiotics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional materials, and specifically relates to a silver dot-modified carbon nitride / urea-perylene imide heterojunction material and a preparation method and application thereof. Background Art

[0002] Antibiotics are a kind of medicinal substance used to treat and prevent bacterial infections. They have been widely used in aquaculture, animal husbandry, medicine and other industries. Studies have shown that humans and animals can only absorb about 30% of the antibiotics they ingest, and the rest are excreted from the body with feces and urine and enter the ecosystem. The presence of antibiotics in the ecosystem has an adverse effect on the growth of certain organisms. In addition, the abuse of antibiotics can also lead to the emergence of drug-resistant bacteria, posing a serious threat to human health and may even cause death; the mortality and morbidity caused by antibiotic pollution are higher than the sum of HIV, prostate cancer and breast cancer. At the same time, the entry of antibiotics into aquatic ecosystems will also threaten the safety of drinking water. Therefore, it is imperative to control antibiotic pollution.

[0003] Traditional methods for treating antibiotic pollution include: electrocoagulation, chemical oxidation, biodegradation, membrane filtration, physical and chemical adsorption, ionizing radiation, etc. The above methods have high operating costs and energy requirements, and the byproducts produced may cause secondary pollution, so they are not suitable for large-scale use. Therefore, there is an urgent need to develop an efficient and environmentally friendly antibiotic degradation method. Semiconductor-based photocatalytic technology can use green and renewable solar energy to produce active substances such as superoxide radicals, hydroxyl radicals, singlet oxygen and holes, and then decompose antibiotics into H2O and CO2. Compared with traditional technologies, this technology has the advantages of simple operation, low energy consumption and no risk of secondary pollution.

[0004] Whether photocatalytic technology can be applied to solve practical problems depends on the utilization rate of solar energy, the separation efficiency of photogenerated carriers and the redox ability of photocatalytic materials. In addition, the cost of mass synthesis of photocatalytic materials, the structural stability and reusability of materials and the biosafety of materials should also be considered. Among the numerous semiconductor photocatalytic materials, organic photocatalysts represented by perylene diimide (PDI) have the characteristics of high solar energy utilization, low cost, easy synthesis, controllable morphology, rich and diverse structures and functional groups, and are therefore highly favored. However, PDI is connected by weak non-covalent interactions (π-π interactions and hydrogen bonds), which are easily decomposed during the photocatalytic reaction, resulting in reduced activity. PDI is connected to urea, and the self-assembled Urea-PDI polymer has high structural stability, and the strong built-in electric field induced by the directional arrangement of macromolecular dipoles can promote the bulk phase separation and transfer of photogenerated carriers, resulting in high photocatalytic performance. However, the high surface recombination rate of photogenerated electron-hole pairs, the weak oxidation ability of photogenerated holes, and the inability to utilize near-infrared light, which accounts for about 50% of the solar spectrum, have restricted the further improvement of the photocatalytic performance of Urea-PDI and limited its practical application in the field of photocatalytic wastewater purification. Summary of the invention

[0005] In order to solve the problems of the above-mentioned prior art, the present invention provides a silver dot modified carbon nitride / urea-perylene imide heterojunction material and a preparation method and application thereof. The silver dot modified carbon nitride / urea-perylene imide heterojunction material has significantly improved photogenerated carrier separation efficiency and redox ability, showing an enhanced full-spectrum catalytic mineralization ability of antibiotics.

[0006] The present invention is achieved through the following technical solutions:

[0007] A silver dot modified carbon nitride / urea-perylene imide heterojunction material, wherein the material is an S-type heterojunction formed by Ag quantum dots, carbon nitride and urea-perylene imide; wherein the carbon nitride is K gradient doped carbon nitride.

[0008] Preferably, the carbon nitride is in the form of nanosheets; and the urea-perylene diimide is in the form of nanorods.

[0009] The method for preparing the silver dot modified carbon nitride / urea-perylene imide heterojunction material of the present invention comprises the following steps:

[0010] S1, grinding and mixing graphite-like carbon nitride powder and KCl powder, calcining the obtained mixture, and then washing, drying, and grinding to obtain carbon nitride powder;

[0011] S2, dispersing carbon nitride powder and urea-perylene imide powder in anhydrous ethanol, stirring, adding AgNO3 powder, stirring, and obtaining a reaction precursor solution;

[0012] S3, subjecting the reaction precursor solution to a solvothermal reaction, washing and drying the obtained product, and obtaining a silver dot-modified carbon nitride / urea-perylene imide heterojunction material.

[0013] Preferably, in S1, the mass ratio of KCl powder to graphite-like carbon nitride powder is 50-2.

[0014] Furthermore, in S1, the calcination temperature is 300-550°C and the time is 1-6 hours.

[0015] Furthermore, in S2, the mass ratio of carbon nitride powder, urea-perylene imide powder and AgNO3 powder is (15-1.875):(15-1.875):(10-0.5).

[0016] Furthermore, in S2, the preparation method of the urea-perylene imide powder is: mixing imidazole, urea, 3,4,9,10-perylenetetracarboxylic dianhydride and anhydrous zinc acetate, heating for reaction, and after the reaction is completed, adding HCl solution for precipitation, and washing and drying the obtained precipitate to obtain urea-perylene imide powder; wherein the molar ratio of urea to 3,4,9,10-perylenetetracarboxylic dianhydride is 0.25 to 4.

[0017] Furthermore, in S3, the temperature of the solvent thermal reaction is 120 to 240° C., and the time is 6 to 24 hours.

[0018] The present invention also provides the use of the silver dot modified carbon nitride / urea-perylene imide heterojunction material as a photocatalyst in degrading organic pollutants in water.

[0019] Preferably, the organic pollutant is an antibiotic.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The silver dot modified carbon nitride / urea-perylene imide heterojunction material of the present invention is a heterojunction formed by Ag quantum dots, carbon nitride and urea-perylene imide. The carbon nitride is K gradient doped carbon nitride, and the introduction of K heteroelement can reduce the band gap energy of carbon nitride and improve its utilization rate of solar energy; K gradient doping induces the formation of a gradient built-in electric field, which can improve the bulk phase separation efficiency of photogenerated carriers; photogenerated electrons that migrate to the surface are captured by nitrogen vacancies, which can inhibit the surface recombination of electrons and holes. The intramolecular macroscopic polarization electric field induced by high crystallinity and dipole orientation in urea-perylene imide polymer can promote the bulk phase separation of photogenerated carriers; at the interface between carbon nitride and urea-perylene imide, the polarization charge is transferred from carbon nitride to urea-perylene imide, forming an interfacial built-in electric field pointing from carbon nitride to urea-perylene imide; at the same time, at the interface, the band edges of carbon nitride and urea-perylene imide bend upward and downward respectively; under the synergistic effect of the interfacial built-in electric field and band bending, the traditional type II heterojunction is transformed into an S-type heterojunction, which can retain electrons and holes with strong redox ability to participate in the photocatalytic reaction. The polarization charge transfer causes the accumulation of free electrons on the urea-perylene imide side, and in order to maintain charge balance, positively charged oxygen vacancies are formed, that is, the polarization charge transfer is conducive to the formation of oxygen vacancies. The Ag quantum dots resonate with the incident photons to generate hot electrons and hot holes, and the hot electrons relax to the conduction band positions of carbon nitride and urea-perylene imide, thereby improving the separation efficiency of hot carriers; the electromagnetic field enhancement generated by the plasmon resonance effect of plasma Ag can accelerate the transition of photogenerated electrons and further promote the bulk phase separation of photogenerated carriers. Under the synergistic effect of the internal gradient built-in electric field of K-gradient doped carbon nitride, the macroscopic polarization electric field in the urea-perylene imide molecule, the interface built-in electric field, the plasma electromagnetic field, the nitrogen vacancy and oxygen vacancy defects and the S-type charge transfer mechanism, the separation efficiency and redox ability of the Ag quantum dot-modified carbon nitride / urea-perylene imide heterojunction photogenerated carriers of the present invention are significantly improved, thereby showing an enhanced ability to catalyze the mineralization of antibiotics across the entire spectrum.

[0022] The present invention prepares K gradient doped carbon nitride through a calcination process, and the introduction of K heterogeneous elements can reduce the band gap energy of carbon nitride and improve its utilization rate of solar energy; K gradient doping induces the formation of a gradient built-in electric field, which can improve the bulk phase separation efficiency of photogenerated carriers; photogenerated electrons migrated to the surface are captured by nitrogen vacancies, which can inhibit the surface recombination of electrons and holes; in addition, the process of K doping by calcination does not destroy the nanosheet structure of carbon nitride. Ag quantum dot-modified carbon nitride / urea-perylene imide heterojunction is prepared by in-situ solvothermal reaction, and the in-situ solvothermal reaction does not destroy the microstructure of carbon nitride and urea-perylene imide. The high temperature, oxygen deficiency and reducing atmosphere provided by the solvothermal reaction lead to the formation of oxygen vacancies on the surface of urea-perylene imide, and the formed oxygen vacancies can be used as capture sites for photogenerated electrons, thereby improving the surface separation efficiency of photogenerated carriers. The defects introduced in the preparation process can effectively inhibit the surface recombination of photogenerated electron-hole pairs, so that the carriers migrated to the surface are fully utilized. The silver dot modified carbon nitride / urea-perylene imide heterojunction prepared by the present invention exhibits full spectrum absorption characteristics and S-type charge transfer mechanism, and exhibits good mineralization ability for antibiotics under visible light and near-infrared light irradiation. The preparation method provided by the present invention is simple to operate, low in cost, and short in time.

[0023] Furthermore, the urea-perylene imide supramolecular polymer prepared by melt imidazole polycondensation reaction has a high degree of crystallinity, can induce the formation of a macroscopic polarization electric field within the molecule, and promote the bulk phase separation of photogenerated electrons and holes. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 is the XRD diagram of the photocatalyst prepared in Comparative Examples 1 to 5 and Example 1 of the present invention;

[0026] Figure 2 It is the diffraction peak magnified in the range of 26° to 29° of the XRD spectrum of the photocatalyst prepared in Comparative Examples 1 to 5 and Example 1 of the present invention;

[0027] Figure 3 FT-IR spectra of the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention;

[0028] Figure 4 is the SEM image of the photocatalyst prepared in Comparative Examples 1 to 2 and Example 1 of the present invention;

[0029] Figure 5 is a SEM image of the photocatalyst prepared in Example 1 of the present invention and a corresponding element mapping image;

[0030] Figure 6 are TEM and HRTEM images of the photocatalyst prepared in Example 1 of the present invention;

[0031] Figure 7 It is the N2 adsorption-desorption isotherm curve and the corresponding pore size distribution curve of the photocatalyst prepared in Comparative Examples 1 to 5 and Example 1 of the present invention;

[0032] Figure 8 It is the EPR spectrum of the photocatalyst prepared in Comparative Examples 1, 2, 4, 5 and Example 1 of the present invention;

[0033] Fig. 9 It is the UV-visible-near infrared diffuse reflectance spectra of the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention;

[0034] Fig.10 is the Kubelka-Munk conversion curve of the photocatalyst prepared in Comparative Examples 1 to 2 of the present invention;

[0035] Fig.11 It is the XPS-VB spectrum of the photocatalyst prepared in Comparative Examples 1 and 2 of the present invention;

[0036] Fig.12 The degradation curves of ciprofloxacin by the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention under visible light irradiation;

[0037] Fig.13 It is the kinetic fitting curve of the photocatalyst prepared in Comparative Examples 1 to 5 and Example 1 of the present invention for catalytic degradation of ciprofloxacin under visible light irradiation;

[0038] Fig.14 It is the total organic carbon (TOC) removal rate of the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention for catalytic degradation of ciprofloxacin under visible light irradiation;

[0039] Fig.15 This is the cycle test result of the visible light catalytic degradation of ciprofloxacin by the photocatalyst prepared in Example 1;

[0040] Fig.16 It is the degradation curve of ciprofloxacin by the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention under near-infrared light irradiation;

[0041] Fig.17 It is the kinetic fitting curve of the photocatalyst prepared in Comparative Examples 1 to 5 and Example 1 of the present invention for catalytic degradation of ciprofloxacin under near-infrared light irradiation;

[0042] Fig.18 The TOC removal rate of the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention when catalyzing the degradation of ciprofloxacin under near-infrared light irradiation;

[0043] Fig.19 This is the result of the cycle experiment of the photocatalyst prepared in Example 1 for near-infrared photocatalytic degradation of ciprofloxacin;

[0044] Fig. 20 is the XRD spectrum of the Ag / KGMCN / UPDI heterojunction photocatalytic material prepared in Example 1 before and after the cyclic reaction;

[0045] Fig.21 is the degradation curve of tetracycline, ofloxacin, norfloxacin, oxytetracycline and oxytetracycline by the photocatalyst prepared in Example 1 under visible light irradiation;

[0046] Fig. 22 is a kinetic fitting curve of the photocatalyst prepared in Example 1 for catalytic degradation of tetracycline, ofloxacin, norfloxacin, oxytetracycline and oxytetracycline under visible light irradiation;

[0047] Fig.23 The TOC removal rate of the photocatalyst prepared in Example 1 under visible light irradiation for catalytic degradation of tetracycline, ofloxacin, norfloxacin, oxytetracycline and oxytetracycline;

[0048] Fig.24 is the degradation curve of tetracycline, ofloxacin, norfloxacin, oxytetracycline and oxytetracycline by the photocatalyst prepared in Example 1 under near-infrared light irradiation;

[0049] Fig.25 The kinetic fitting curve of the photocatalyst prepared in Example 1 for catalytic degradation of tetracycline, ofloxacin, norfloxacin, oxytetracycline and oxytetracycline under near-infrared light irradiation;

[0050] Fig.26 The TOC removal rate of the photocatalyst prepared in Example 1 when catalyzing the degradation of tetracycline, ofloxacin, norfloxacin, oxytetracycline and oxytetracycline under near-infrared light irradiation;

[0051] Fig. 27 The active species capture experimental results of the photocatalyst prepared in Example 1 for photocatalytic degradation of ciprofloxacin under visible light irradiation;

[0052] Fig.28 The active species capture experimental results of the photocatalyst prepared in Example 1 for photocatalytic degradation of ciprofloxacin under near-infrared light irradiation;

[0053] Fig.29 is the photoluminescence spectrum of the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention;

[0054] Fig.30 It is the high-resolution XPS K 2p spectra of the photocatalysts prepared in Comparative Example 1 and Comparative Example 5;

[0055] Fig.31 This is a mechanism diagram of the photocatalytic degradation of antibiotics by the photocatalyst prepared in Example 1 under full solar spectrum irradiation. DETAILED DESCRIPTION

[0056] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0057] The silver dot modified carbon nitride / urea-perylene imide heterojunction material of the present invention is a heterojunction composite material formed by Ag quantum dots, carbon nitride and urea-perylene imide, and the mass ratio of the three is (0.013-0.51) g:(0.15-0.60) g:(0.15-0.60) g.

[0058] Among them, Ag quantum dots belong to the isometric crystal system, with unit cell parameters of 4.0862×4.0862×4.0862, 90.0×90.0×90.0, space point group of Fm-3m(225), and a size of about 4.5nm; carbon nitride is K-gradient doped carbon nitride, containing nitrogen vacancy defects, and exhibiting a nanosheet morphology; urea-perylene diimide contains oxygen vacancy defects, and exhibits an irregular nanorod morphology.

[0059] The preparation method of the silver dot modified carbon nitride / urea-perylene imide heterojunction photocatalyst comprises the following steps:

[0060] S1, grinding and mixing graphite-like carbon nitride powder and KCl powder, calcining the obtained mixture, and then washing, drying, and grinding to obtain carbon nitride powder;

[0061] S2, dispersing carbon nitride powder and urea-perylene imide powder in anhydrous ethanol, stirring, adding AgNO3 powder, stirring, and obtaining a reaction precursor solution;

[0062] S3, subjecting the reaction precursor solution to a solvothermal reaction, washing and drying the obtained product, and obtaining a silver dot-modified carbon nitride / urea-perylene imide heterojunction material.

[0063] In some embodiments of the present invention, in S1, the mass ratio of the KCl powder to the graphite-like carbon nitride powder is 50-2, the grinding time is 1-6 hours, the calcination temperature is 300-550°C, the heating rate is 1-5°C, and the insulation time is 1-6 hours.

[0064] In S1 of the present invention, melamine is used as a raw material to prepare graphite-like carbon nitride powder by high-temperature thermal polymerization reaction, specifically: taking melamine powder, heating it to 550°C, keeping it warm for a period of time and then cooling it to room temperature; grinding the obtained light yellow product to obtain graphite-like carbon nitride powder; wherein the heating rate is 5 to 20°C·min -1 , the insulation time is 2 to 6 hours.

[0065] In S2 of the present invention, urea and 3,4,9,10-perylenetetracarboxylic dianhydride are used as raw materials, imidazole is used as a solvent, and anhydrous zinc acetate is used as a catalyst. The urea-perylene imide polymer is prepared by a melt imidazole polycondensation reaction. Specifically, imidazole, urea, 3,4,9,10-perylenetetracarboxylic dianhydride and anhydrous zinc acetate are mixed, heated for reaction, and after the reaction is completed, HCl solution is added for precipitation. The obtained precipitate is washed and dried to obtain urea-perylene imide powder; wherein the molar ratio of urea to 3,4,9,10-perylenetetracarboxylic dianhydride is 0.25-4, and in the reaction system, the molar concentrations of urea, 3,4,9,10-perylenetetracarboxylic dianhydride and anhydrous zinc acetate are 0.125-2 mmol·g -1 咪唑 , 0.125~2mmol·g -1 咪唑 , 0.125~2mmol·g -1 咪唑 , the heating temperature is 120-160°C, the reaction time is 3-12h, and the amount of HCl introduced is 150-400mL.

[0066] In some embodiments of the present invention, the mass concentrations of carbon nitride, urea-perylene imide and AgNO3 in the reaction precursor solution in S2 are 15 to 1.875 g·L -1 15~1.875g·L -1 and 10~0.5g·L -1 , that is, the mass ratio is (15~1.875):(15~1.875):(10~0.5).

[0067] In some embodiments of the present invention, in S3, the filling ratio of the solvent thermal reaction is 40% to 80%, the reaction temperature is 120 to 240° C., and the reaction time is 6 to 24 hours.

[0068] Experimental results show that the silver dot-modified carbon nitride / urea-perylene imide heterojunction material of the present invention exhibits an S-type charge transfer mechanism, exhibits full-spectrum absorption characteristics, and can mineralize antibiotics under full-spectrum (visible light and near-infrared light) irradiation.

[0069] The antibiotics are, for example, ciprofloxacin, tetracycline, ofloxacin, norfloxacin, oxytetracycline or metronidazole. After 60 minutes of visible light irradiation, the silver dot-modified carbon nitride / urea-perylene imide heterojunction material can achieve mineralization efficiencies of 89.17%, 86.73%, 74.58%, 63.84%, 72.26% and 51.76% for ciprofloxacin, tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole, respectively. After 240 minutes of near-infrared light irradiation, the mineralization efficiencies of 78.95%, 76.85%, 72.12%, 58.70%, 67.59% and 47.16% for ciprofloxacin, tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole, respectively.

[0070] Comparative Example 1

[0071] K-gradient-doped carbon nitride (KGMCN) photocatalyst was prepared by a two-step calcination method:

[0072] Step 1: Weigh 10 g of melamine powder, place it in a corundum crucible with a lid, and place it in the center of the muffle furnace; -1 The heating rate is from room temperature to 550°C, and after keeping the temperature for 4 hours, the furnace is cooled to room temperature; the light yellow product is ground with an agate mortar until there is no particle feeling when touched by fingers, and graphite-like carbon nitride powder, abbreviated as MCN, is obtained, which is collected for later use;

[0073] Step 2: Weigh 1.5 g of the MCN powder prepared above and 10 g of KCl powder, grind them in an alumina mortar for 2 h to obtain a uniformly dispersed mixture; place the mixture in a corundum crucible with a lid, and place it in the center of a muffle furnace at 2 °C min -1 The heating rate is from room temperature to 550°C, and the product is kept at this temperature for 3 hours and then cooled to room temperature with the furnace; the product is washed with deionized water until the KCl in the product is completely removed, and then washed with anhydrous ethanol for 3 times; after drying at 70°C for 24 hours, the dark yellow product is ground with an agate mortar until there is no particle feeling when touched by fingers, thereby obtaining K-gradient-doped carbon nitride powder, abbreviated as KGMCN.

[0074] Comparative Example 2

[0075] Preparation of urea-perylene diimide (UPDI) photocatalyst via melt imidazole polymerization:

[0076] Step 1: Into a 500 mL three-necked flask, 5.0 g of imidazole, 0.12 g (2.0 mmol) of urea, 0.78 g (2 mmol) of 3,4,9,10-perylenetetracarboxylic dianhydride and 0.37 g (2 mmol) of anhydrous zinc acetate were added successively;

[0077] Step 2: Under magnetic stirring, heat the above system to 140°C in an oil bath and react for 5 hours.

[0078] Step 3: After cooling to room temperature, add 250 mL of 1 mol·L -1 HCl solution, and stir magnetically until no solid precipitates;

[0079] Step 4: Wash the resulting red precipitate several times with deionized water and + Detect until the washing solution no longer contains Cl - The product was dried under vacuum at 60°C for 24 hours to obtain urea-perylene diimide photocatalyst, abbreviated as UPDI.

[0080] Comparative Example 3:

[0081] Preparation of Ag / KGMCN photocatalyst via in situ solvothermal reaction:

[0082] Step 1: Disperse 0.3 g of KGMCN powder prepared in Comparative Example 1 into 40 mL of anhydrous ethanol, stir magnetically for 30 min, add 0.18 g of AgNO3 powder to the suspension, continue magnetic stirring for 2 h, and obtain a uniformly mixed reaction precursor solution;

[0083] Step 2: The obtained reaction precursor solution was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, heated from room temperature to 150°C, kept warm for 12 hours, and cooled to room temperature with the furnace. The obtained precipitate was washed three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain the Ag / KGMCN photocatalyst.

[0084] Comparative Example 4:

[0085] Preparation of Ag / UPDI photocatalyst via in situ solvothermal reaction:

[0086] Step 1: Disperse 0.3 g of UPDI powder prepared in Comparative Example 2 into 40 mL of anhydrous ethanol, stir magnetically for 30 min, add 0.18 g of AgNO3 powder into the suspension, continue to stir magnetically for 2 h, and obtain a uniformly mixed reaction precursor solution;

[0087] Step 2: The obtained reaction precursor solution was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, heated from room temperature to 150°C, kept warm for 12 hours, and cooled to room temperature with the furnace. The obtained precipitate was washed three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain the Ag / UPDI photocatalyst.

[0088] Comparative Example 5:

[0089] Preparation of KGMCN / UPDI photocatalyst via solvothermal reaction:

[0090] Step 1: Disperse 0.3 g of KGMCN powder prepared in Comparative Example 1 into 40 mL of anhydrous ethanol, and stir magnetically for 30 min. Then, add 0.3 g of UPDI powder prepared in Comparative Example 2 into the suspension, and continue to stir magnetically for 2 h to obtain a uniformly mixed reaction precursor solution.

[0091] Step 2: The obtained reaction precursor solution was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, heated from room temperature to 150°C, kept warm for 12 hours, and cooled to room temperature with the furnace. The obtained precipitate was washed three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain the KGMCN / UPDI photocatalyst.

[0092] Embodiment 1:

[0093] Preparation of Ag / KGMCN / UPDI heterojunction photocatalysts via in situ solvothermal reaction:

[0094] Step 1: Disperse 0.3 g of KGMCN powder prepared in Comparative Example 1 into 40 mL of anhydrous ethanol, stir magnetically for 30 min, add 0.3 g of UPDI powder prepared in Comparative Example 2 into the suspension, and continue to stir magnetically for 30 min;

[0095] Step 2: Then, 0.18 g of AgNO3 powder was added to the above suspension and magnetically stirred for 2 h to obtain a uniformly mixed reaction precursor solution;

[0096] Step 3: The obtained reaction precursor solution was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, heated from room temperature to 150°C, kept warm for 12 hours, and cooled to room temperature with the furnace. The obtained precipitate was washed three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain the Ag / KGMCN / UPDI heterojunction photocatalyst.

[0097] Embodiment 2:

[0098] Step 1: Weigh 10 g of melamine powder, place it in a corundum crucible with a lid, and place it in the center of the muffle furnace; -1The temperature was raised to 550°C at a rate of 1.50 °C, kept at this temperature for 6 hours, and then cooled to room temperature with the furnace; the obtained light yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, and graphite-like carbon nitride powder, abbreviated as MCN, was obtained, which was collected for later use;

[0099] Step 2: Weigh 0.5 g of the MCN powder prepared in step 1 and 15 g of KCl powder, grind them in an alumina mortar for 1 h to obtain a uniformly dispersed mixture; place the above mixture in a corundum crucible with a lid, and place it in the center of a muffle furnace at 1 °C min -1 The heating rate was raised from room temperature to 550°C, kept at this temperature for 4 hours, and then cooled to room temperature in the furnace; the KCl in the obtained product was washed with deionized water until it was completely removed, and then washed with anhydrous ethanol for 3 times; after drying at 70°C for 24 hours, the obtained dark yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, thus obtaining K-gradient doped carbon nitride powder, abbreviated as KGMCN;

[0100] Step 3: Place 2 g imidazole, 0.06 g urea, 0.51 g 3,4,9,10-perylenetetracarboxylic dianhydride and 0.22 g anhydrous zinc acetate in a 500 mL three-necked flask and react at 120 °C for 3 h under magnetic stirring; after cooling to room temperature, add 400 mL 1 mol·L -1 HCl solution, stirred magnetically until no solid precipitates; the resulting red precipitate is washed with deionized water until the supernatant no longer contains Cl - The product was then washed several times with dimethyl sulfoxide until the washing liquid became colorless; the washed product was vacuum dried at 60°C for 24h to obtain urea-perylene diimide powder, abbreviated as UPDI;

[0101] Step 4: Weigh 0.15 g of the KGMCN powder prepared in step 2 and 0.30 g of the UPDI powder prepared in step 3, disperse them in 50 mL of anhydrous ethanol, stir them magnetically for 30 min, add 0.02 g of AgNO3 powder, and then stir them magnetically for 2 h to obtain a uniformly mixed reaction precursor solution;

[0102] Step 5: The reaction precursor solution obtained in step 4 was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, reacted at 120°C for 12 hours, cooled to room temperature, washed the precipitate three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain a silver dot-modified carbon nitride / urea-perylene imide heterojunction photocatalyst.

[0103] Embodiment 3:

[0104] Step 1: Weigh 10 g of melamine powder, put it in a corundum crucible with a lid, and place it in the center of the muffle furnace; -1The temperature was raised to 550°C at a rate of 1.50 °C, kept at this temperature for 4 hours, and then cooled to room temperature with the furnace; the obtained light yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, and graphite-like carbon nitride powder, abbreviated as MCN, was obtained, which was collected for later use;

[0105] Step 2: Weigh 0.8 g of the MCN powder prepared in step 1 and 5 g of KCl powder, grind them in an alumina mortar for 3 h to obtain a uniformly dispersed mixture; place the above mixture in a corundum crucible with a lid, and place it in the center of a muffle furnace at 3 °C min -1 The heating rate was raised from room temperature to 550°C, kept at this temperature for 3 hours, and then cooled to room temperature in the furnace; the KCl in the obtained product was washed with deionized water until it was completely removed, and then washed with anhydrous ethanol for 3 times; after drying at 70°C for 24 hours, the obtained dark yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, thus obtaining K-gradient doped carbon nitride powder, abbreviated as KGMCN;

[0106] Step 3: 6 g imidazole, 0.12 g urea, 0.47 g 3,4,9,10-perylenetetracarboxylic dianhydride and 0.35 g anhydrous zinc acetate were placed in a 500 mL three-necked flask and reacted at 160 °C for 6 h under magnetic stirring; after cooling to room temperature, 350 mL 1 mol·L -1 HCl solution, stirred magnetically until no solid precipitates; the resulting red precipitate is washed with deionized water until the supernatant no longer contains Cl - The product was then washed several times with dimethyl sulfoxide until the washing liquid became colorless; the washed product was vacuum dried at 60°C for 24h to obtain urea-perylene diimide powder, abbreviated as UPDI;

[0107] Step 4: Weigh 0.30 g of the KGMCN powder prepared in step 2 and 0.36 g of the UPDI powder prepared in step 3, disperse them in 70 mL of anhydrous ethanol, stir them magnetically for 30 min, add 0.14 g of AgNO3 powder, and then stir them magnetically for 2 h to obtain a uniformly mixed reaction precursor solution;

[0108] Step 5: The reaction precursor solution obtained in step 4 was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, reacted at 150°C for 15 hours, cooled to room temperature, washed the precipitate three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain a silver dot-modified carbon nitride / urea-perylene imide heterojunction photocatalyst.

[0109] Embodiment 4:

[0110] Step 1: Weigh 10 g of melamine powder, place it in a corundum crucible with a lid, and place it in the center of the muffle furnace; -1The temperature was raised to 550°C at a rate of 1.50 °C, kept at this temperature for 2 hours, and then cooled to room temperature with the furnace; the obtained light yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, and graphite-like carbon nitride powder, abbreviated as MCN, was obtained, which was collected for later use;

[0111] Step 2: Weigh 1.2 g of the MCN powder prepared in step 1 and 10 g of KCl powder, grind them in an alumina mortar for 5 h to obtain a uniformly dispersed mixture; place the above mixture in a corundum crucible with a lid, and place it in the center of a muffle furnace at 5 °C min -1 The heating rate was raised from room temperature to 550°C, kept at this temperature for 1 hour, and then cooled to room temperature in the furnace; the KCl in the obtained product was washed with deionized water until it was completely removed, and then washed with anhydrous ethanol for 3 times; after drying at 70°C for 24 hours, the obtained dark yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, thus obtaining K-gradient doped carbon nitride powder, abbreviated as KGMCN;

[0112] Step 3: 8 g imidazole, 0.18 g urea, 0.44 g 3,4,9,10-perylenetetracarboxylic dianhydride and 0.44 g anhydrous zinc acetate were placed in a 500 mL three-necked flask and reacted at 140 °C for 12 h under magnetic stirring; after cooling to room temperature, 300 mL 1 mol·L -1 HCl solution, stirred magnetically until no solid precipitates; the resulting red precipitate is washed with deionized water until the supernatant no longer contains Cl - The product was then washed several times with dimethyl sulfoxide until the washing liquid became colorless; the washed product was vacuum dried at 60°C for 24h to obtain urea-perylene diimide powder, abbreviated as UPDI;

[0113] Step 4: Weigh 0.45 g of the KGMCN powder prepared in step 2 and 0.42 g of the UPDI powder prepared in step 3, disperse them in 80 mL of anhydrous ethanol, stir them magnetically for 30 min, add 0.28 g of AgNO3 powder, and then stir them magnetically for 2 h to obtain a uniformly mixed reaction precursor solution;

[0114] Step 5: The reaction precursor solution obtained in step 4 was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, reacted at 180°C for 18 hours, cooled to room temperature, washed the precipitate three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain a silver dot-modified carbon nitride / urea-perylene imide heterojunction photocatalyst.

[0115] Embodiment 5:

[0116] Step 1: Weigh 10 g of melamine powder, place it in a corundum crucible with a lid, and place it in the center of a muffle furnace; -1The temperature was raised to 550°C at a rate of 1.50 °C, kept at this temperature for 5 hours, and then cooled to room temperature with the furnace; the obtained light yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, and graphite-like carbon nitride powder, abbreviated as MCN, was obtained, which was collected for later use;

[0117] Step 2: Weigh 1.5 g of the MCN powder prepared in step 1 and 20 g of KCl powder, grind them in an alumina mortar for 2 h to obtain a uniformly dispersed mixture; place the above mixture in a corundum crucible with a lid, and place it in the center of a muffle furnace at 4 °C min -1 The heating rate was raised from room temperature to 550°C, kept at this temperature for 2 hours, and then cooled to room temperature in the furnace; the KCl in the obtained product was washed with deionized water until it was completely removed, and then washed with anhydrous ethanol for 3 times; after drying at 70°C for 24 hours, the obtained dark yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, thus obtaining K-gradient doped carbon nitride powder, abbreviated as KGMCN;

[0118] Step 3: 7 g imidazole, 0.24 g urea, 0.42 g 3,4,9,10-perylenetetracarboxylic dianhydride and 0.57 g anhydrous zinc acetate were placed in a 500 mL three-necked flask and reacted at 150 °C for 9 h under magnetic stirring; after cooling to room temperature, 250 mL 1 mol·L -1 HCl solution, stirred magnetically until no solid precipitates; the resulting red precipitate is washed with deionized water until the supernatant no longer contains Cl - The product was then washed several times with dimethyl sulfoxide until the washing liquid became colorless; the washed product was vacuum dried at 60°C for 24h to obtain urea-perylene diimide powder, abbreviated as UPDI;

[0119] Step 4: Weigh 0.60 g of the KGMCN powder prepared in step 2 and 0.54 g of the UPDI powder prepared in step 3, disperse them in 60 mL of anhydrous ethanol, stir them magnetically for 30 min, add 0.36 g of AgNO3 powder, and then stir them magnetically for 2 h to obtain a uniformly mixed reaction precursor solution;

[0120] Step 5: The reaction precursor solution obtained in step 4 was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, reacted at 210°C for 24 hours, cooled to room temperature, washed the precipitate three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain a silver dot-modified carbon nitride / urea-perylene imide heterojunction photocatalyst.

[0121] Embodiment 6:

[0122] Step 1: Weigh 10 g of melamine powder, put it in a corundum crucible with a lid, and place it in the center of the muffle furnace; -1The temperature was raised to 550°C at a rate of 1.50 °C, kept at this temperature for 3 hours, and then cooled to room temperature with the furnace; the obtained light yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, and graphite-like carbon nitride powder, abbreviated as MCN, was obtained, which was collected for later use;

[0123] Step 2: Weigh 1.8 g of the MCN powder prepared in step 1 and 16 g of KCl powder, grind them in an alumina mortar for 4 h to obtain a uniformly dispersed mixture; place the above mixture in a corundum crucible with a lid, and place it in the center of a muffle furnace at 2 °C min -1 The heating rate was raised from room temperature to 550°C, kept at this temperature for 5 hours, and then cooled to room temperature in the furnace; the KCl in the obtained product was washed with deionized water until it was completely removed, and then washed with anhydrous ethanol for 3 times; after drying at 70°C for 24 hours, the obtained dark yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, thus obtaining K-gradient doped carbon nitride powder, abbreviated as KGMCN;

[0124] Step 3: Place 5 g imidazole, 0.09 g urea, 0.47 g 3,4,9,10-perylenetetracarboxylic dianhydride and 0.69 g anhydrous zinc acetate in a 500 mL three-necked flask and react at 160 °C for 10 h under magnetic stirring; after cooling to room temperature, add 200 mL 1 mol·L -1 HCl solution, stirred magnetically until no solid precipitates; the resulting red precipitate is washed with deionized water until the supernatant no longer contains Cl - The product was then washed several times with dimethyl sulfoxide until the washing liquid became colorless; the washed product was vacuum dried at 60°C for 24h to obtain urea-perylene diimide powder, abbreviated as UPDI;

[0125] Step 4: Weigh 0.55 g of the KGMCN powder prepared in step 2 and 0.45 g of the UPDI powder prepared in step 3, disperse them in 40 mL of anhydrous ethanol, stir them magnetically for 30 min, add 0.45 g of AgNO3 powder, and then stir them magnetically for 2 h to obtain a uniformly mixed reaction precursor solution;

[0126] Step 5: The reaction precursor solution obtained in step 4 was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, reacted at 240°C for 6 hours, cooled to room temperature, washed the precipitate three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain a silver dot-modified carbon nitride / urea-perylene imide heterojunction photocatalyst.

[0127] Embodiment 7:

[0128] Step 1: Weigh 10 g of melamine powder, place it in a corundum crucible with a lid, and place it in the center of the muffle furnace; -1The temperature was raised to 550°C at a rate of 1.50 °C, kept at this temperature for 2 hours, and then cooled to room temperature with the furnace; the obtained light yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, and graphite-like carbon nitride powder, abbreviated as MCN, was obtained, which was collected for later use;

[0129] Step 2: Weigh 2.1 g of the MCN powder prepared in step 1 and 12 g of KCl powder, grind them in an alumina mortar for 6 h to obtain a uniformly dispersed mixture; place the above mixture in a corundum crucible with a lid, and place it in the center of a muffle furnace at 3 °C min -1 The heating rate was raised from room temperature to 550°C, kept at this temperature for 6 hours, and then cooled to room temperature in the furnace; the KCl in the obtained product was washed with deionized water until it was completely removed, and then washed with anhydrous ethanol for 3 times; after drying at 70°C for 24 hours, the obtained dark yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, thus obtaining K-gradient doped carbon nitride powder, abbreviated as KGMCN;

[0130] Step 3: 3 g imidazole, 0.15 g urea, 0.45 g 3,4,9,10-perylenetetracarboxylic dianhydride and 0.73 g anhydrous zinc acetate were placed in a 500 mL three-necked flask and reacted at 130 °C for 8 h under magnetic stirring; after cooling to room temperature, 250 mL 1 mol·L -1 HCl solution, stirred magnetically until no solid precipitates; the resulting red precipitate is washed with deionized water until the supernatant no longer contains Cl - The product was then washed several times with dimethyl sulfoxide until the washing liquid became colorless; the washed product was vacuum dried at 60°C for 24h to obtain urea-perylene diimide powder, abbreviated as UPDI;

[0131] Step 4: Weigh 0.50 g of the KGMCN powder prepared in step 2 and 0.15 g of the UPDI powder prepared in step 3, disperse them in 50 mL of anhydrous ethanol, stir them magnetically for 30 min, add 0.80 g of AgNO3 powder, and then stir them magnetically for 2 h to obtain a uniformly mixed reaction precursor solution;

[0132] Step 5: The reaction precursor solution obtained in step 4 was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, reacted at 200°C for 12 hours, cooled to room temperature, washed the precipitate three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain a silver dot-modified carbon nitride / urea-perylene imide heterojunction photocatalyst.

[0133] Embodiment 8:

[0134] Step 1: Weigh 10 g of melamine powder, place it in a corundum crucible with a lid, and place it in the center of the muffle furnace; -1The temperature was raised to 550°C at a rate of 1.50 °C, kept at this temperature for 4 hours, and then cooled to room temperature with the furnace; the obtained light yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, and graphite-like carbon nitride powder, abbreviated as MCN, was obtained, which was collected for later use;

[0135] Step 2: Weigh 2.4 g of the MCN powder prepared in step 1 and 8 g of KCl powder, grind them in an alumina mortar for 4 h to obtain a uniformly dispersed mixture; place the above mixture in a corundum crucible with a lid, and place it in the center of a muffle furnace at 2 °C min -1 The heating rate was raised from room temperature to 550°C, kept at this temperature for 4 hours, and then cooled to room temperature in the furnace; the KCl in the obtained product was washed with deionized water until it was completely removed, and then washed with anhydrous ethanol for 3 times; after drying at 70°C for 24 hours, the obtained dark yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, thus obtaining K-gradient doped carbon nitride powder, abbreviated as KGMCN;

[0136] Step 3: 4 g imidazole, 0.20 g urea, 0.49 g 3,4,9,10-perylenetetracarboxylic dianhydride and 0.88 g anhydrous zinc acetate were placed in a 500 mL three-necked flask and reacted at 120 °C for 6 h under magnetic stirring; after cooling to room temperature, 300 mL 1 mol·L -1 HCl solution, stirred magnetically until no solid precipitates; the resulting red precipitate is washed with deionized water until the supernatant no longer contains Cl - The product was then washed several times with dimethyl sulfoxide until the washing liquid became colorless; the washed product was vacuum dried at 60°C for 24h to obtain urea-perylene diimide powder, abbreviated as UPDI;

[0137] Step 4: Weigh 0.28 g of the KGMCN powder prepared in step 2 and 0.60 g of the UPDI powder prepared in step 3, disperse them in 60 mL of anhydrous ethanol, stir them magnetically for 30 min, add 0.69 g of AgNO3 powder, and then stir them magnetically for 2 h to obtain a uniformly mixed reaction precursor solution;

[0138] Step 5: The reaction precursor solution obtained in step 4 was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, reacted at 160°C for 8 hours, cooled to room temperature, washed the precipitate three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain a silver dot-modified carbon nitride / urea-perylene imide heterojunction photocatalyst.

[0139] Embodiment 9:

[0140] Step 1: Weigh 10 g of melamine powder, place it in a corundum crucible with a lid, and place it in the center of a muffle furnace; -1The temperature was raised to 550°C at a rate of 1.50 °C, kept at this temperature for 6 hours, and then cooled to room temperature with the furnace; the obtained light yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, and graphite-like carbon nitride powder, abbreviated as MCN, was obtained, which was collected for later use;

[0141] Step 2: Weigh 2.5 g of the MCN powder prepared in step 1 and 6 g of KCl powder, grind them in an alumina mortar for 2 h to obtain a uniformly dispersed mixture; place the above mixture in a corundum crucible with a lid, and place it in the center of a muffle furnace at 4 °C min -1 The heating rate was raised from room temperature to 550°C, kept at this temperature for 1 hour, and then cooled to room temperature in the furnace; the KCl in the obtained product was washed with deionized water until it was completely removed, and then washed with anhydrous ethanol for 3 times; after drying at 70°C for 24 hours, the obtained dark yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, thus obtaining K-gradient doped carbon nitride powder, abbreviated as KGMCN;

[0142] Step 3: 6 g imidazole, 0.21 g urea, 0.52 g 3,4,9,10-perylenetetracarboxylic dianhydride and 0.66 g anhydrous zinc acetate were placed in a 500 mL three-necked flask and reacted at 150 °C for 4 h under magnetic stirring; after cooling to room temperature, 150 mL 1 mol·L -1 HCl solution, stirred magnetically until no solid precipitates; the resulting red precipitate is washed with deionized water until the supernatant no longer contains Cl - The product was then washed several times with dimethyl sulfoxide until the washing liquid became colorless; the washed product was vacuum dried at 60°C for 24h to obtain urea-perylene diimide powder, abbreviated as UPDI;

[0143] Step 4: Weigh 0.36 g of the KGMCN powder prepared in step 2 and 0.24 g of the UPDI powder prepared in step 3, disperse them in 40 mL of anhydrous ethanol, stir them magnetically for 30 min, add 0.57 g of AgNO3 powder, and then stir them magnetically for 2 h to obtain a uniformly mixed reaction precursor solution;

[0144] Step 5: The reaction precursor solution obtained in step 4 was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, reacted at 140°C for 16 hours, cooled to room temperature, washed the precipitate three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain a silver dot-modified carbon nitride / urea-perylene imide heterojunction photocatalyst.

[0145] Embodiment 10:

[0146] Step 1: Weigh 10 g of melamine powder, place it in a corundum crucible with a lid, and place it in the center of the muffle furnace; -1The temperature was raised to 550°C at a rate of 1.50 °C, kept at this temperature for 3 hours, and then cooled to room temperature with the furnace; the obtained light yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, and graphite-like carbon nitride powder, abbreviated as MCN, was obtained, which was collected for later use;

[0147] Step 2: Weigh 1.5 g of the MCN powder prepared in step 1 and 18 g of KCl powder, grind them in an alumina mortar for 3 h to obtain a uniformly dispersed mixture; place the above mixture in a corundum crucible with a lid, and place it in the center of a muffle furnace at 3 °C min -1 The heating rate was raised from room temperature to 550°C, kept at this temperature for 3 hours, and then cooled to room temperature in the furnace; the KCl in the obtained product was washed with deionized water until it was completely removed, and then washed with anhydrous ethanol for 3 times; after drying at 70°C for 24 hours, the obtained dark yellow product was ground with an agate mortar until there was no particle feeling when touched by fingers, thus obtaining K-gradient doped carbon nitride powder, abbreviated as KGMCN;

[0148] Step 3: 8 g imidazole, 0.18 g urea, 0.46 g 3,4,9,10-perylenetetracarboxylic dianhydride and 0.55 g anhydrous zinc acetate were placed in a 500 mL three-necked flask and reacted at 140 °C for 5 h under magnetic stirring; after cooling to room temperature, 250 mL 1 mol·L -1 HCl solution, stirred magnetically until no solid precipitates; the resulting red precipitate is washed with deionized water until the supernatant no longer contains Cl - The product was then washed several times with dimethyl sulfoxide until the washing liquid became colorless; the washed product was vacuum dried at 60°C for 24h to obtain urea-perylene diimide powder, abbreviated as UPDI;

[0149] Step 4: Weigh 0.15 g of the KGMCN powder prepared in step 2 and 0.51 g of the UPDI powder prepared in step 3, disperse them in 80 mL of anhydrous ethanol, stir them magnetically for 30 min, add 0.45 g of AgNO3 powder, and then stir them magnetically for 2 h to obtain a uniformly mixed reaction precursor solution;

[0150] Step 5: The reaction precursor solution obtained in step 4 was transferred to a 100 mL hydrothermal reactor with a polytetrafluoroethylene liner, reacted at 210°C for 22 hours, cooled to room temperature, washed the precipitate three times with deionized water and anhydrous ethanol respectively, and dried at 70°C for 24 hours to obtain a silver dot-modified carbon nitride / urea-perylene imide heterojunction photocatalyst.

[0151] The accompanying drawings in the present invention are described in detail below.

[0152] Figure 1The XRD patterns of the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention are shown in FIG. In the XRD pattern of the photocatalyst prepared in Comparative Example 1, the diffraction peaks at about 13° and 27.5° correspond to the (100) and (002) crystal planes of the graphite-like carbon nitride, respectively, indicating that K gradient doping does not change the network structure of carbon nitride; in the XRD pattern of the photocatalyst prepared in Comparative Example 2, the appearance of the diffraction peak at about 27.1° is attributed to the intermolecular π-π stacking interaction. From the XRD spectrum, it can be seen that the photocatalysts prepared in Comparative Examples 3, 4 and 5 are composed of Ag and KGMCN, Ag and UPDI, KGMCN and UPDI, respectively. In the XRD spectrum of the photocatalysts prepared in Comparative Examples 3 and 4, the diffraction peaks at about 38.1°, 44.3° and 64.4° correspond to the (111), (200) and (220) crystal planes of cubic Ag (JCPDS No. 04-0783), respectively, and its space group is Fm-3m (225), and the unit cell parameters are 4.0862×4.0862×4.0862, 90.0×90.0×90.0. In the XRD spectrum of the photocatalyst prepared in Example 1, the characteristic diffraction peaks of Ag, KGMCN and UPDI can be observed simultaneously, indicating that the present invention successfully prepared the Ag / KGMCN / UPDI heterojunction photocatalytic material through in-situ solvent thermal reaction.

[0153] Figure 2 It is the diffraction peak magnified in the range of 26° to 29° of the XRD spectrum of the photocatalyst prepared in Comparative Examples 1 to 5 and Example 1 of the present invention. It can be seen from the figure that after Ag, KGMCN and UPDI are compounded, the main diffraction peaks of KGMCN and UPDI are shifted to the high angle direction, indicating that there is a strong chemical interaction between the three, rather than a simple physical mixture.

[0154] Figure 3 FT-IR spectra of the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention. In the FT-IR spectrum of the KGMCN photocatalyst prepared in Comparative Example 1, 3400 to 3000 cm -1 The wide absorption band in the range of 1750-1000 cm corresponds to the stretching vibration of OH and NH bonds. -1 A series of characteristic absorption peaks in the range correspond to the stretching vibration of aromatic CN heterocycles, 809cm -1 The sharp characteristic absorption peak at about 2170 cm-1 corresponds to the bending vibration of the tris-triazine ring. Compared with the graphite-like carbon nitride reported in the literature, the FT-IR spectrum of KGMCN prepared in Comparative Example 1 shows a peak at about 2170 cm-1. -1 An additional characteristic absorption peak can be observed at 1763 cm -1、1682cm -1 and 1587cm -1 The characteristic absorption peaks at correspond to the -N-(C=O)-N- bond, -N-(C=O)-C- bond and the stretching vibration mode of the benzene ring skeleton, respectively. The FT-IR spectra of Ag / KGMCN and Ag / UPDI prepared in Comparative Examples 3 and 4 are similar to the FT-IR spectra of KGMCN and UPDI, respectively. The FT-IR spectra of KGMCN / UPDI and Ag / KGMCN / UPDI photocatalysts prepared in Comparative Example 5 and Example 1 can simultaneously observe the characteristic absorption peaks of KGMCN and UPDI. Compared with single-component KGMCN, in the FT-IR spectra of Ag / KGMCN, KGMCN / UPDI and Ag / KGMCN / UPDI, 2170cm -1 The characteristic absorption peak at is significantly weakened, further indicating that there is a strong interaction among Ag, KGMCN and UPDI.

[0155] Figure 4 a, b, and c are SEM images of KGMCN, UPDI, and Ag / KGMCN / UPDI photocatalysts prepared in Comparative Example 1, Comparative Example 2, and Example 1, respectively. As can be seen from the figure, KGMCN exhibits a nanosheet morphology with wrinkles on the surface, and UPDI exhibits an irregular nanorod morphology. From the SEM image of Ag / KGMCN / UPDI, it can be seen that UPDI nanorods are tightly attached to the surface of KGMCN nanosheets to form a heterogeneous structure; due to their small size, the presence of Ag quantum dots is not observed in the figure.

[0156] Figure 5 This is a SEM image and corresponding element mapping of the Ag / KGMCN / UPDI heterojunction photocatalyst prepared in Example 1. As can be seen from the figure, Ag, K, C, N, and O elements exist in the heterojunction, corresponding to its composition.

[0157] Figure 6 Figures a to c are TEM images of Ag / KGMCN / UPDI prepared in Example 1, in which nanosheets, nanorods and dot-like morphologies can be observed, among which the dot-like morphologies are Ag quantum dots. Figure 6 Figures d to f are the corresponding HRTEM images. KGMCN and UPDI did not detect obvious lattice fringes. The lattice fringes with a crystal plane spacing of 0.236 nm correspond to the (111) crystal plane of Ag. The average size of the Ag quantum dots is about 4.5 nm.

[0158] Figure 7The N2 adsorption-desorption isotherms and corresponding pore size distribution curves of the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention are shown in Table 1. The BET specific surface areas of KGMCN, UPDI, Ag / KGMCN, Ag / UPDI, KGMCN / UPDI, and Ag / KGMCN / UPDI are 12.125 m 2 ·g -1 、20.136m 2 ·g -1 、13.218m 2 ·g -1 、17.817m 2 ·g -1 、18.597m 2 ·g -1 、18.182m 2 ·g -1 The BET specific surface area of ​​Ag / KGMCN / UPDI heterojunction photocatalyst is slightly lower than that of single-component UPDI, but significantly larger than that of single-component KGMCN. The increase in BET specific surface area indicates that Ag / KGMCN / UPDI can provide more active sites for photocatalytic reactions. The total pore volumes of KGMCN, UPDI, Ag / KGMCN, Ag / UPDI, KGMCN / UPDI, and Ag / KGMCN / UPDI are 0.3453 cm 3 ·g -1 、0.5415cm 3 ·g -1 、0.4852cm 3 ·g -1 、0.4453cm 3 ·g -1 、0.5780cm 3 ·g -1 、0.5547cm 3 ·g -1 The average pore diameters are 19.342nm, 15.198nm, 16.493nm, 13.201nm, 16.538nm and 19.011nm respectively. The total pore volume of Ag / KGMCN / UPDI heterojunction photocatalyst is larger than that of single-component KGMCN and UPDI, and the average pore diameter is slightly lower than that of KGMCN, but significantly larger than that of single-component UPDI. The increase in the total pore volume and average pore diameter is also conducive to the occurrence of photocatalytic reaction.

[0159] Figure 8The EPR spectra of the photocatalysts prepared in Comparative Examples 1, 2, 4, 5 and Example 1 of the present invention. Obvious EPR signals can be observed for all samples at g = 2.0036. The EPR signal peaks of the photocatalysts prepared in Comparative Examples 1 and 2 correspond to single electron capture at nitrogen vacancy sites and oxygen vacancy sites, respectively, indicating that nitrogen vacancy and oxygen vacancy defects exist in KGMCN and UPDI, respectively. The EPR signals of Ag / UPDI and KGMCN / UPDI prepared in Comparative Examples 4 and 5 are significantly higher than those of single-component UPDI, indicating that solvent thermal treatment is conducive to the formation of oxygen vacancies in UPDI. In addition, XPS ( Fig.30 ) The test results show that at the interface of KGMCN and UPDI, the polarized charge is transferred from KGMCN to UPDI, and free electrons accumulate on the UPDI side, inducing the formation of positively charged oxygen vacancies to maintain charge balance, resulting in a higher defect concentration in KGMCN / UPDI than in UPDI. After the three-phase composite of Ag, KGMCN and UPDI, the EPR signal of the catalyst is further enhanced, indicating that the defect concentration is further increased, which can provide more active sites for the photocatalytic reaction.

[0160] Fig. 9 The UV-visible-near-infrared diffuse reflectance spectra of the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention. As can be seen from the figure, the KGMCN photocatalyst prepared in Comparative Example 1 can only absorb ultraviolet light and part of the visible light, and its light absorption edge is about 500nm. The appearance of the Urbach absorption tail in the range of 500 to 800nm ​​is attributed to the formation of shallow capture states induced by nitrogen vacancy defects. The light response range of the UPDI photocatalyst prepared in Comparative Example 2 is significantly wider than that of KGMCN, and its light absorption edge can reach 700nm. Ag quantum dots have obvious localized surface plasmon resonance effects. Therefore, the visible-near-infrared light absorption of the Ag / KGMCN and Ag / UPDI photocatalysts prepared in Comparative Examples 3 and 4 is significantly enhanced, which improves the utilization rate of the photocatalyst for solar energy. It can be seen from the UV-visible-near-infrared diffuse reflectance spectrum of the Ag / KGMCN photocatalyst that the characteristic absorption peak of the localized surface plasmon resonance of the Ag quantum dots is located at about 500nm. The UV-visible-near-infrared diffuse reflectance spectrum of the Ag / KGMCN / UPDI heterojunction photocatalyst prepared in Example 1 is similar to that of Ag / UPDI, that is, the Ag / KGMCN / UPDI heterojunction photocatalyst also exhibits full-spectrum absorption characteristics and can fully utilize solar energy for photocatalytic reactions.

[0161] Fig.10 The Kubelka-Munk conversion curves of the photocatalysts prepared in Comparative Example 1 and Comparative Example 2 are shown in Table 1. According to the formula: αhν=A(hν-E g ) n / 2(For KGMCN and UPDI, the value of n is 4). The calculated band gaps of KGMCN and UPDI are 2.23 eV and 1.78 eV, respectively.

[0162] Fig.11 This is the XPS-VB spectrum of the photocatalyst prepared in Comparative Examples 1 and 2 of the present invention. As can be seen from the figure, the valence band potentials of KGMCN and UPDI are +1.40eV and +1.75eV respectively. According to the formula: E CB =E VB -E g The calculated conduction band potentials of KGMCN and UPDI are -0.83 eV and -0.03 eV, respectively.

[0163] Fig.12 The degradation curves of ciprofloxacin by the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention under visible light irradiation are shown in Figure 1. The initial concentration of the ciprofloxacin solution is 20 mg·L -1 The concentration of photocatalyst in the reaction system is 0.5 g·L -1 , the visible light source is a 500W xenon lamp + 420nm cutoff filter. As can be seen from the figure, the reaction activity of the Ag / KGMCN / UPDI heterojunction photocatalyst prepared in Example 1 is significantly higher than that of the single-component and two-component materials. After 60 minutes of visible light irradiation, the degradation efficiency of KGMCN and UPDI prepared in Comparative Examples 1 and 2 for ciprofloxacin was 29.07% and 23.06%, respectively; under the same reaction conditions, the degradation efficiency of Ag / KGMCN, Ag / UPDI and KGMCN / UPDI prepared in Comparative Examples 3 to 5 for ciprofloxacin increased to 39.70%, 55.69% and 75.51%, respectively; Ag / KGMCN / UPDI has the highest degradation efficiency for ciprofloxacin, which can reach 92.80%.

[0164] Fig.13 The kinetic curves of the degradation of ciprofloxacin by the photocatalysts prepared in comparative examples 1 to 5 and Example 1 of the present invention under visible light irradiation are shown in the figure. As can be seen from the figure, under visible light irradiation, the degradation process of ciprofloxacin by the photocatalysts prepared in the present invention follows the pseudo-first-order kinetic equation. The degradation rates of ciprofloxacin by KGMCN and UPDI prepared in comparative examples 1 and 2 are 0.0056min and 0.12min, respectively. -1 、0.0038min -1 The degradation rates of ciprofloxacin by the two-component Ag / KGMCN, Ag / UPDI and KGMCN / UPDI prepared in Comparative Examples 3 to 5 were increased to 0.0083 min -1 、0.013min -1 and 0.023min -1The degradation rate of ciprofloxacin by the Ag / KGMCN / UPDI heterojunction prepared in Example 1 was the fastest, which was 0.043 min -1 , which are 7.68, 11.32, 5.18, 3.31 and 1.87 times of KGMCN, UPDI, Ag / KGMCN, Ag / UPDI and KGMCN / UPDI respectively.

[0165] Fig.14 The TOC removal rates of the photocatalysts prepared in comparative examples 1 to 5 and Example 1 of the present invention for photocatalytic degradation of ciprofloxacin under visible light irradiation are shown. After 60 minutes of visible light irradiation, the TOC removal rates of the single-component KGMCN and UPDI for photocatalytic degradation of ciprofloxacin were 19.10% and 12.08%, respectively; under the same reaction conditions, the TOC removal rates of the two-component Ag / KGMCN, Ag / UPDI, and KGMCN / UPDI for photocatalytic degradation of ciprofloxacin increased to 33.22%, 49.08%, and 66.89%, respectively; the TOC removal rate of the Ag / KGMCN / UPDI heterojunction photocatalytic degradation of ciprofloxacin prepared in Example 1 can reach 89.17%, and the significantly increased TOC removal rate indicates that the heterojunction photocatalyst prepared by the present invention has a good mineralization ability for ciprofloxacin under visible light irradiation.

[0166] Fig.15 The results of the cyclic experiment of the photocatalyst prepared in Example 1 for the degradation of ciprofloxacin under visible light catalysis. During the 1st to 6th cycle reaction, after 60 minutes of visible light irradiation, the degradation efficiency of ciprofloxacin by the Ag / KGMCN / UPDI heterojunction photocatalyst was 92.80%, 92.13%, 91.65%, 90.76%, 90.16% and 87.62%, respectively. After 6 cycles, the degradation efficiency of ciprofloxacin by Ag / KGMCN / UPDI was only reduced by about 5.18%, indicating that it has good cyclic stability.

[0167] Fig.16 The degradation curves of ciprofloxacin by the photocatalysts prepared in Comparative Examples 1 to 5 and Example 1 of the present invention under near-infrared light irradiation are shown in Figure 1. The initial concentration of the ciprofloxacin solution is 20 mg·L -1 The concentration of photocatalyst in the reaction system is 0.5 g·L -1, the near-infrared light source is a 500W xenon lamp + 800nm ​​cut-off filter. As can be seen from the figure, the reaction activity of the Ag / KGMCN / UPDI heterojunction photocatalyst prepared in Example 1 to degrade ciprofloxacin under near-infrared light irradiation is also higher than that of single-component and two-component materials. Due to limited light absorption, after 240 minutes of near-infrared light irradiation, the degradation efficiency of KGMCN, UPDI and KGMCN / UPDI prepared in Comparative Examples 1, 2 and 5 on ciprofloxacin is only 13.86%, 26.70% and 37.12%; after loading Ag quantum dots, under the same reaction conditions, the degradation efficiency of Ag / KGMCN and Ag / UPDI prepared in Comparative Examples 3 and 4 on ciprofloxacin increased by 62.45% and 47.05% respectively; Ag / KGMCN / UPDI has the highest degradation efficiency on ciprofloxacin, which can reach 81.60%.

[0168] Fig.17 The kinetic curves of the degradation of ciprofloxacin by photocatalysts prepared in comparative examples 1 to 5 and Example 1 under near-infrared light irradiation are shown in the figure. As can be seen from the figure, under near-infrared light irradiation, the degradation process of ciprofloxacin by the photocatalyst prepared in the present invention also follows the pseudo-first-order kinetic equation. The degradation rates of ciprofloxacin by KGMCN, UPDI, and KGMCN / UPDI prepared in comparative examples 1, 2, and 5 are 0.0005 min -1 、0.0012min -1 and 0.0018min -1 The degradation rates of ciprofloxacin by Ag / KGMCN and Ag / UPDI prepared in Comparative Examples 3 and 4 were increased to 0.0038 min -1 and 0.0026min -1 The Ag / KGMCN / UPDI heterojunction prepared in Example 1 has the fastest degradation rate of ciprofloxacin, reaching 0.0067min -1 , which are 13.4, 5.58, 1.76, 2.58 and 3.72 times of KGMCN, UPDI, Ag / KGMCN, Ag / UPDI and KGMCN / UPDI respectively.

[0169] Fig.18The TOC removal rates of the photocatalysts prepared in comparative examples 1 to 5 and Example 1 of the present invention for photocatalytic degradation of ciprofloxacin under near-infrared light irradiation are shown. After 240 minutes of near-infrared light irradiation, the TOC removal rates of KGMCN, UPDI and KGMCN / UPDI for photocatalytic degradation of ciprofloxacin were 10.01%, 17.37% and 28.40%, respectively; under the same reaction conditions, the TOC removal rates of Ag / KGMCN and Ag / UPDI for photocatalytic degradation of ciprofloxacin increased to 55.43% and 41.47%, respectively; the TOC removal rate of the Ag / KGMCN / UPDI heterojunction photocatalytic degradation of ciprofloxacin prepared in Example 1 can reach 78.95%, and the significantly increased TOC removal rate indicates that the heterojunction photocatalyst prepared by the present invention also has good mineralization ability for ciprofloxacin under near-infrared light irradiation.

[0170] Fig.19 The results of the cyclic experiment of the photocatalyst prepared in Example 1 for the near-infrared photocatalytic degradation of ciprofloxacin. During the 1st to 6th cycle reactions, after 240 minutes of near-infrared light irradiation, the degradation efficiency of ciprofloxacin by the Ag / KGMCN / UPDI heterojunction photocatalyst was 81.73%, 81.13%, 80.02%, 79.06%, 78.85% and 77.41%, respectively. After 6 cycles, the degradation efficiency of ciprofloxacin by Ag / KGMCN / UPDI was only reduced by about 4.32%, indicating that it also has good cyclic stability under near-infrared light irradiation.

[0171] Fig. 20 The XRD patterns of the Ag / KGMCN / UPDI heterojunction photocatalyst material prepared in Example 1 before and after the cyclic reaction. After 6 cycles of reaction, the XRD pattern of the Ag / KGMCN / UPDI heterojunction did not change significantly, indicating that the Ag / KGMCN / UPDI heterojunction photocatalyst material prepared in the present invention has good structural stability.

[0172] Fig.21 The degradation curves of tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole under visible light irradiation by the photocatalyst prepared in Example 1 are shown. After 60 minutes of visible light irradiation, the degradation efficiencies of tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole by the Ag / KGMCN / UPDI heterojunction photocatalyst prepared in Example 1 are 94.08%, 86.57%, 76.26%, 85.68% and 62.52%, respectively. The results show that the heterojunction photocatalyst prepared by the present invention also has a good degradation effect on other antibiotics under visible light irradiation.

[0173] Fig. 22The kinetic fitting curves of the photocatalyst prepared in Example 1 for the degradation of tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole under visible light irradiation. Under visible light irradiation, the degradation rates of tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole by the Ag / KGMCN / UPDI heterojunction photocatalyst prepared in Example 1 were 0.0553 min -1 、0.0326min -1 、0.0240min -1 、0.0346min -1 and 0.0163min -1 .

[0174] Fig.23 The TOC removal rate of tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole catalytically degraded by the photocatalyst prepared in Example 1 under visible light irradiation. After 60 minutes of visible light irradiation, the mineralization rates of tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole by the Ag / KGMCN / UPDI heterojunction photocatalyst prepared in Example 1 were 86.73%, 74.58%, 63.84%, 72.26% and 51.76%, respectively.

[0175] Fig.24 The degradation curves of tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole by the photocatalyst prepared in Example 1 under near-infrared light irradiation are shown. After 240 minutes of near-infrared light irradiation, the degradation efficiencies of the Ag / KGMCN / UPDI heterojunction photocatalyst prepared in Example 1 for tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole were 90.93%, 81.46%, 70.99%, 84.65% and 61.40%, respectively. The results show that the heterojunction photocatalyst prepared in the present invention also has a good degradation effect on other antibiotics under near-infrared light irradiation.

[0176] Fig.25 The kinetic fitting curves of the photocatalyst prepared in Example 1 for catalytic degradation of tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole under near-infrared light irradiation. Under near-infrared light irradiation, the degradation rates of tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole by the Ag / KGMCN / UPDI heterojunction photocatalyst prepared in Example 1 were 0.0098 min -1 、0.0070min -1 、0.0051min -1 、0.0072min -1 and 0.0037min -1 .

[0177] Fig.26The TOC removal rate of tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole catalytically degraded by the photocatalyst prepared in Example 1 under near-infrared light irradiation. After 240 minutes of near-infrared light irradiation, the mineralization rates of tetracycline, ofloxacin, norfloxacin, oxytetracycline and metronidazole by the Ag / KGMCN / UPDI heterojunction photocatalyst prepared in Example 1 were 76.85%, 72.12%, 58.70%, 67.59% and 47.16%, respectively.

[0178] Fig. 27 The active species capture experimental results of the photocatalyst prepared in Example 1 for photocatalytic degradation of ciprofloxacin under visible light irradiation, potassium dichromate (K2Cr2O7, 1mmol·L -1 ), ethylenediaminetetraacetic acid (EDTA, 1mmol·L -1 ), p-benzoquinone (p-BQ, 1mmol·L -1 ), tert-butyl alcohol (TBA, 1mmol·L -1 ), manganese dioxide (MnO2, 1mmol·L -1 ) are used as electrons (e - ), hole (h + ), superoxide radicals (·O2 - ), hydroxyl radical (·OH) and hydrogen peroxide (H2O2) scavengers. After introducing K2Cr2O7, EDTA, p-BQ, TBA and MnO2 into the reaction system, the degradation rate of ciprofloxacin by Ag / KGMCN / UPDI heterojunction increased from 0.043min -1 Reduced to 0.013min -1 、0.030min -1 、0.008min -1 、0.017min -1 、0.021min -1 , indicating that the main active species during the catalytic degradation of ciprofloxacin by the obtained heterojunction under visible light irradiation is ·O2 - 、e - and OH, H2O2 and h + Second.

[0179] Fig.28 The results of the active species capture experiment of the photocatalyst prepared in Example 1 for photocatalytic degradation of ciprofloxacin under near-infrared light irradiation. After introducing K2Cr2O7, EDTA, p-BQ, TBA and MnO2 into the reaction system, the degradation rate of ciprofloxacin by Ag / KGMCN / UPDI heterojunction increased from 0.0067min to 0.117min. -1 Reduced to 0.0019min respectively -1 、0.0021min -1、0.0008min -1 、0.0056min -1 、0.0061min -1 , indicating that the order of the roles played by the various active species during the catalytic degradation of ciprofloxacin by the obtained heterojunction under near-infrared light irradiation is as follows: O2 - >e - >h + >·OH>H2O2.

[0180] Fig.29 It is the photoluminescence spectrum of the photocatalyst prepared in Comparative Examples 1 to 5 and Example 1 of the present invention, and the excitation wavelength is 370nm. As can be seen from the figure, a strong fluorescence emission peak can be detected in the KGMCN photocatalyst prepared in Comparative Example 1 at about 476nm, and the UPDI photocatalyst prepared in Comparative Example 2 does not show obvious fluorescence characteristics. The intensity of the fluorescence emission peak of the Ag / KGMCN and KGMCN / UPDI photocatalysts prepared in Comparative Examples 3 and 5 is significantly lower than that of the single-component KGMCN, indicating that the composite with Ag and UPDI can improve the separation efficiency of KGMCN photogenerated electron-hole pairs. The intensity of the fluorescence emission peak of Ag / KGMCN / UPDI prepared in Example 1 is further reduced compared with Ag / KGMCN and KGMCN / UPDI, indicating that the three-phase composite can further improve the separation efficiency of photogenerated carriers.

[0181] Fig.30 The high-resolution XPS K 2p spectra of the photocatalysts prepared in Examples 1 and 5 of the present invention are shown in Figure 2. For KGMCN, the characteristic peaks at 295.36 eV and 292.64 eV correspond to the 2p 1 / 2 and 2p 3 / 2 After complexing with UPDI, the binding energy of K element increases, indicating that its charge density decreases, that is, after KGMCN and UPDI are complexed, the polarization charge is transferred from KGMCN to UPDI.

[0182] Fig.31This is a mechanism diagram of the photocatalytic degradation of antibiotics by the photocatalyst prepared in Example 1 of the present invention under full solar spectrum irradiation. Under sunlight irradiation, KGMCN and UPDI are excited, and electrons transition from the valence band to the conduction band, leaving holes in the valence band. Due to the K gradient doping, a gradient built-in electric field (GIEF) will be formed inside KGMCN to promote the bulk phase separation of photogenerated carriers; electrons migrating to the surface can be captured by nitrogen vacancies, thereby improving the surface separation efficiency of photogenerated carriers. Due to the high crystallinity and the directional arrangement of macromolecular dipoles, an intramolecular macroscopic polarization electric field (IMPEF) is formed inside UPDI, and combined with the charge capture effect of oxygen vacancies, UPDI also has a high carrier separation rate. At the interface, the polarization charge is transferred from KGMCN to UPDI, thereby forming an interface built-in electric field (IBIEF) directed from KGMCN to UPDI. At the same time, at the interface, the band edges of KGMCN and UPDI are bent upward and downward, respectively. Under the synergistic effect of the built-in electric field and band bending at the interface, the photogenerated holes of KGMCN and the photogenerated electrons of UPDI combine at the interface to form excitons or are annihilated, and the electrons and holes with higher redox ability are retained. That is, the traditional type II heterojunction is transformed into an S-type mechanism. In addition, Ag quantum dots and incident photons generate plasmon hot electrons and hot holes through resonance, and the conduction bands of KGMCN and UPDI provide an energy level platform for hot electron relaxation, thereby improving the separation efficiency of hot carriers. The enhanced plasma electromagnetic field (PEMF) induced by the localized surface plasmon resonance effect of Ag quantum dots can accelerate electron transitions and further promote the bulk phase separation of photogenerated electrons and holes. Under the synergistic effect of the gradient built-in electric field, intramolecular polarization electric field, interface built-in electric field, plasma electromagnetic field, nitrogen vacancy and oxygen vacancy defects and S-type mechanism, the separation efficiency and redox ability of photogenerated carriers of the Ag / KGMCN / UPDI heterojunction are significantly improved. The photogenerated electrons of KGMCN react with O2 to generate ·O2 - Free radicals, O2 - Free radicals can further react with electrons and holes to transform into H2O2 and 1 O2 and H2O2 can dissociate to form ·OH free radicals. The hot holes generated by Ag quantum dots can react with H2O to generate ·OH free radicals. The excitons formed by the combination of electrons and holes at the interface can interact with O2 and transform into 1 O2. Antibiotics and holes, O2 - Free radicals, OH radicals, 1 O2 and other active substances react and are decomposed into H2O and CO2.

Claims

1. A silver dot modified carbon nitride / urea-perylene imide heterojunction material, characterized in that: The material is an S-type heterojunction formed by Ag quantum dots, carbon nitride and urea-perylene imide; wherein the carbon nitride is K gradient-doped carbon nitride.

2. The silver dot modified carbon nitride / urea-perylene imide heterojunction material according to claim 1, characterized in that: The carbon nitride is in the form of nanosheets; and the urea-perylene imide is in the form of nanorods.

3. The method for preparing the silver dot modified carbon nitride / urea-perylene imide heterojunction material according to claim 1 or 2, characterized in that: The following steps are involved: S1, grinding and mixing graphite-like carbon nitride powder and KCl powder, calcining the obtained mixture, and then washing, drying, and grinding to obtain carbon nitride powder; S2, dispersing carbon nitride powder and urea-perylene imide powder in anhydrous ethanol, stirring, adding AgNO3 powder, stirring, and obtaining a reaction precursor solution; S3, subjecting the reaction precursor solution to a solvothermal reaction, washing and drying the obtained product, and obtaining a silver dot-modified carbon nitride / urea-perylene imide heterojunction material.

4. The method for preparing the silver dot modified carbon nitride / urea-perylene imide heterojunction material according to claim 3, characterized in that: In S1, the mass ratio of KCl powder to graphite-like carbon nitride powder is 50-2.

5. The method for preparing the silver dot modified carbon nitride / urea-perylene imide heterojunction material according to claim 3, characterized in that: In S1, the calcination temperature is 300-550°C and the time is 1-6 hours.

6. The method for preparing the silver dot modified carbon nitride / urea-perylene imide heterojunction material according to claim 3, characterized in that: In S2, the mass ratio of carbon nitride powder, urea-perylene imide powder and AgNO3 powder is (15-1.875):(15-1.875):(10-0.5).

7. The method for preparing the silver dot modified carbon nitride / urea-perylene imide heterojunction material according to claim 3, characterized in that: In S2, the preparation method of the urea-perylene imide powder is: imidazole, urea, 3,4,9,10-perylenetetracarboxylic dianhydride and anhydrous zinc acetate are mixed, heated for reaction, and after the reaction is completed, HCl solution is added for precipitation, and the obtained precipitate is washed and dried to obtain urea-perylene imide powder; wherein the molar ratio of urea to 3,4,9,10-perylenetetracarboxylic dianhydride is 0.25 to 4.

8. The method for preparing the silver dot modified carbon nitride / urea-perylene imide heterojunction material according to claim 3, characterized in that: In S3, the temperature of the solvent thermal reaction is 120 to 240° C., and the time is 6 to 24 hours.

9. Use of the silver dot modified carbon nitride / urea-perylene imide heterojunction material according to claim 1 or 2 as a photocatalyst for degrading organic pollutants in water.

10. The use according to claim 9, characterized in that: The organic pollutant is an antibiotic.